Suppressor of Cytokine Signaling 2 Regulates Retinal Pigment Epithelium Metabolism by Enhancing Autophagy - Liu, Xi-Yuan; Lu, Rui; Chen, Jing; Wang, Jie; Qian, Hong-Mei; Chen, Gang; Wu, Rong-Han; Chi, Zai-Long (Frontiers in Neuroscience, 2021)
Retinal pigment epithelium (RPE) serves critical functions in maintaining retinal homeostasis. An important function of RPE is to degrade photoreceptor outer segment fragments daily to maintain photoreceptor function and longevity throughout life. An Impairment of RPE functions such as metabolic regulation, leads to the development of age-related macular degeneration (AMD) and inherited retinal degenerative diseases. As substrate recognition subunit of a ubiquitin ligase complex, suppressor of cytokine signaling 2 (SOCS2) specifically binds to substrates for ubiquitination and negatively regulates growth hormone signaling. Herein, we explore the role of SOCS2 in the metabolic regulation of autophagy in RPE cells. SOCS2 knockout mice exhibited irregular morphological deposits between the RPE and Bruch’s membrane. Both in vivo and in vitro experiments showed that RPE cells lacking SOCS2 displayed impaired autophagy, which could be recovered by re-expressing SOCS2. SOCS2 recognizes ubiquitylated proteins and participates in the formation of autolysosome by binding with autophagy receptors and lysosome-associated membrane proteins LAMP-2, thereby regulating the phosphorylation of glycogen synthase kinase 3 (GSK3and mammalian target of rapamycin (mTOR) during the autophagic process. Our results imply that SOCS2 participates in ubiquitin-autophagy-lysosomal pathway and enhances autophagy by regulating GSK3 and mTOR. This study provides a potential therapeutic target for AMD.